2020
DOI: 10.1002/bies.201900246
|View full text |Cite
|
Sign up to set email alerts
|

The Fluidity of the Bacterial Outer Membrane Is Species Specific

Abstract: The outer membrane (OM) is an essential barrier that guards Gram‐negative bacteria from diverse environmental insults. Besides functioning as a chemical gatekeeper, the OM also contributes towards the strength and stiffness of cells and allows them to sustain mechanical stress. Largely influenced by studies of Escherichia coli, the OM is viewed as a rigid barrier where OM proteins and lipopolysaccharides display restricted mobility. Here the discussion is extended to other bacterial species, with a focus on My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The low fluidity of the OMV coating is in line with the common imagination of the bacterial OM to be highly rigid. [ 56 ] However, considering the fluidity of OMV‐derived lipid bilayers from either E. coli [ 57 ] or other Gram‐negative species, [ 55 ] the fluidity of this coating appears particularly low, which gives the impression that the functionality of lipids has been dramatically decreased. This is explainable by the additional presence of LPS and proteins among the OMV PLs.…”
Section: Resultsmentioning
confidence: 99%
“…The low fluidity of the OMV coating is in line with the common imagination of the bacterial OM to be highly rigid. [ 56 ] However, considering the fluidity of OMV‐derived lipid bilayers from either E. coli [ 57 ] or other Gram‐negative species, [ 55 ] the fluidity of this coating appears particularly low, which gives the impression that the functionality of lipids has been dramatically decreased. This is explainable by the additional presence of LPS and proteins among the OMV PLs.…”
Section: Resultsmentioning
confidence: 99%
“…This model can accommodate a number of scenarios for how JspA and LppA jointly respond to envelope stress: for instance, LppA may enable the proper folding or positioning of JspA in the membrane, or misfolding of LppA may directly induce JspA's proteolytic activity. In particular, the complex physical properties of the outer membrane (Cao & Wall, 2020;Sun et al, 2022) necessitate multiple regulatory checkpoints, and LppA may sense its integrity, analogous to the E. coli RcsF lipoprotein (Tata et al, 2021), and transmit disturbances to JspA. Alternatively, LppA may monitor or participate in the crosslink between the outer membrane and the cell wall (Godessart et al, 2021), and disruptions in the process are relayed to JspA.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Cazzola et al [ 41 ], a close correlation was observed between the increase in E. coli adhesion to eukaryotic cells and the decrease in cell membrane fluidity of these bacteria. In another study carried out on four selected bacterial species, it was shown that, together with the entry into the biofilm (sedentary) phase, microorganisms accumulate saturated fatty acids in their cell membranes, leading to a decrease in their membranes’ fluidity [ 42 ]. Identical observations were made in another article [ 43 ], where, using Pseudomonas aeruginosa as a model organism, the participation of extracellular vesicles in membrane stiffening and promotion of biofilm formation was additionally noticed.…”
Section: Discussionmentioning
confidence: 99%